2022
DOI: 10.1080/13670050.2022.2064191
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of SES and multilinguistic experience on cognitive development: a longitudinal data analysis of multilingual and monolingual adolescents from the SCAMP cohort

Abstract: Previous research has shown that cognitive development is sensitive to socio-economic status (SES) and multilinguistic experiences. However, these effects are difficult to disentangle and SES may modulate the effects of multilingualism. The present study used data from a large cohort of pupils who took part in the Study of Cognition, Adolescents and Mobile Phones (SCAMP) at ages 11–12 (T1) and 13–15 years old (T2). Cognitive measures were derived from tasks of cognitive flexibility, verbal, spatial and visuo-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…A further recent study conducted by Alarcon (2022) indicated a positive effect of bilingualism on working memory tasks requiring attentional control, namely test anxiety. In addition, Filippi et al (2022) showed consistent results concerning a bilingual advantage and supported the view in which bilingualism has a positive effect on working memory tasks, namely those measuring visual-spatial abilities.…”
Section: Bilingualism: Advantages and Disadvantagessupporting
confidence: 73%
“…A further recent study conducted by Alarcon (2022) indicated a positive effect of bilingualism on working memory tasks requiring attentional control, namely test anxiety. In addition, Filippi et al (2022) showed consistent results concerning a bilingual advantage and supported the view in which bilingualism has a positive effect on working memory tasks, namely those measuring visual-spatial abilities.…”
Section: Bilingualism: Advantages and Disadvantagessupporting
confidence: 73%
“…In the TMT, a significant effect of Balanced Proficiency emerged, revealing that individuals with greater balance between their two most proficient languages exhibited a reduced B:A ratio, indicative of enhanced flexibility. Literature examining the performance of bilinguals on the TMT is limited, but studies usually do not report an effect, owing to the fact that the switching and visual attention involved in the TMT are arguably not trained through multiple language control (Filippi et al 2022;Stasenko et al 2017;Torres et al 2022). Nevertheless, there are a few studies reporting benefits for bilinguals in different age groups (Bialystok 2010;Estanga et al 2017), but these usually evaluate the performance in Trail A and Trail B separately, while the B:A ratio is in fact a more accurate measure of CF (Kopp 2011).…”
Section: Relationship Between Language Experience and Cognitive Contr...mentioning
confidence: 99%
“…In fact, for speakers of the dominant language, bilingual programs help develop proficiency in two languages with no adverse effects on literacy or fluency development in their first language (Cummins, 2009). For all students, bilingual programs yield great academic success (Cummins, 2009), greater cognitive flexibility (Filippi et al, 2022), and focus (Fitzgerald & Schutte, 2010). Towards these goals, under an alter-globalized vision, all classrooms would become multilingual spaces.…”
Section: Transitioning From Neoliberal English and Dominant Language ...mentioning
confidence: 99%